Предмет: Математика,
автор: zhucatayaldan2
Вычислите способом, который использовал Гаусс при сложении: -1-2-3-4-5-6-7-8-9-10-11
1*(-2)+2*(-2)+3*(-2)+4*(-2)+5*(-2)+6*(-2)
6:(-3)+9:(-3)+12:(-3)+15:(-3)+18:(-3)+21:(-3)
Ответы
Автор ответа:
0
-1-2-3-4-5-6-7-8-9-10-11=-1-11=-12 -2-10=-12 -3-9=-12 -4-8=-12 -5-7=-12
=-6
2)1*(-2)+2*(-2)+3*(-2)+4*(-2)+5*(-2)*6*(-2)=-2(1+2+3+4+5+6)=-2*21=-42
3)6:(-3)+9:(-3)+12:(-3)+15:(-3)+18:(-3)+21:(-3)=(6+9+12+15+18+21):(-3)-81:(-3)=-27
Вот всё
=-6
2)1*(-2)+2*(-2)+3*(-2)+4*(-2)+5*(-2)*6*(-2)=-2(1+2+3+4+5+6)=-2*21=-42
3)6:(-3)+9:(-3)+12:(-3)+15:(-3)+18:(-3)+21:(-3)=(6+9+12+15+18+21):(-3)-81:(-3)=-27
Вот всё
Похожие вопросы
Предмет: Биология,
автор: leraaradionova
Предмет: Английский язык,
автор: AndreyLadnev
Предмет: Математика,
автор: anastasiaudovcenko83
Предмет: Алгебра,
автор: GreedySquirrel
Предмет: Экономика,
автор: Сашулька20011